2021
DOI: 10.1002/jcad.12412
|View full text |Cite
|
Sign up to set email alerts
|

Child‐centered play therapy and adverse childhood experiences: A randomized controlled trial

Abstract: There is a preponderance of evidence that adverse childhood experiences (ACEs) result in harmful physical, learning, social, emotional, and behavioral health outcomes during childhood, with far reaching effects lasting across the lifespan. The cumulative effect of childhood adversity and its relationship to childhood trauma represent an urgent call to action among stakeholders, yet treatment studies are rare. The purpose of this randomized controlled trial was to explore the impact of child‐centered play thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Through another SCRD study, Schoonover and Perryman (2023) found that participants (N = 5) experienced improvements in externalizing behavior problems during the play therapy treatment process. In a recent randomized control trial, Ray et al (2022) found that CCPT was an effective treatment for children with multiple ACEs, evidenced by participants' statistically and practically significant improvements in empathy, social competence, and self-regulation. Conroy and Perryman (2022) suggested that CCPT is a powerful intervention for strengthening children's autonomic nervous system regulatory abilities because play therapists provide continual coregulatory support, and help the child develop understandings of their emotions so that they may eventually engage in self-regulation.…”
Section: Child Centered Play Therapy and Adverse Childhood Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Through another SCRD study, Schoonover and Perryman (2023) found that participants (N = 5) experienced improvements in externalizing behavior problems during the play therapy treatment process. In a recent randomized control trial, Ray et al (2022) found that CCPT was an effective treatment for children with multiple ACEs, evidenced by participants' statistically and practically significant improvements in empathy, social competence, and self-regulation. Conroy and Perryman (2022) suggested that CCPT is a powerful intervention for strengthening children's autonomic nervous system regulatory abilities because play therapists provide continual coregulatory support, and help the child develop understandings of their emotions so that they may eventually engage in self-regulation.…”
Section: Child Centered Play Therapy and Adverse Childhood Experiencesmentioning
confidence: 99%
“…The common factors model aligns with humanistic child counseling approaches, such as child‐centered play therapy (CCPT; Landreth, 2023; Ray, 2011), which recognize therapeutic relationship factors (congruence, positive regard, empathic understanding) as primary therapeutic change mechanisms. Researchers have reported evidence that CCPT is an effective intervention to address behavioral, social, and emotional problems among children who experience ACEs (Haas & Ray, 2020; Ray et al., 2022; Schoonover & Perryman, 2023). Because the therapeutic relationship is the primary theoretical change mechanism of CCPT, it is important to consider how children with multiple ACEs and complex trauma experience and engage within the therapeutic relationship.…”
Section: Childhood Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, children dealing with neurodevelopmental challenges (Guest & Ohrt, 2018; Salter et al, 2016), anxiety (Baggerly, 2004; Stulmaker & Ray, 2015), depressive symptoms (Baggerly, 2004), or behavioral challenges (Bratton et al, 2013; Phipps & Post, 2019) are also referred to play therapy services. Although play therapists are most often trained to work with children who have experienced such challenges and adverse experiences (Ray et al, 2022), the work can take a cumulative toll on one’s mental health and well-being. Glisson and Williams (2015) emphasized the importance of streamlining referral processes while maintaining awareness of practitioner needs in order to improve both clinical and professional development outcomes.…”
Section: Play Therapists’ Job Satisfactionmentioning
confidence: 99%